Bringing sustainable agricultural intensification practices and technologies to scale through campaign-based extension approaches: lessons from Africa Soil Health Consortium. Issue 5 (3rd September 2022) - Kansiime, Monica K.; Njunge, Rahab; Okuku, Innocent; Baars, Edward; Alokit, Christine; Duah, Solomon; Gakuo, Stephanie; Karanja, Lucy; Mchana, Abigael; Mibei, Henry; Musebe, Richard; Romney, Dannie; et al.
ABSTRACT: Sustainable agricultural intensification (SAI) practices have been developed with the aim of increasing agricultural productivity. However, most of them are not achieving their potential because of low adoption, linked to limited extension support to make them known and accessible by end-users. This paper reviews the effectiveness of the Africa Soil Health Consortium (ASHC) extension-based campaigns, contributing knowledge for formulating novel and cost-effective extension approaches. Results show that ASHC campaigns achieved scale of farmer reach and spurred adoption of promoted SAI technologies. Adoption levels for a range of practices were at least 20%, which favourably compares with reported adoption rates for the training and visit extension approach; 1-7% and 11-21% for complex and simple practices respectively. In comparison to a single channel, exposure to multiple communication approaches was associated with higher uptake of promoted practices and technologies, and also increased participation of men, women and youth, by addressing inherent differences in access to, proficiency with, and preferences of communication channels. Success factors associated with ASHC campaigns were; the deployment of multiple and complementary information channels; harnessing public-private partnerships to establish sustainable input supply chains; and development of localized content and fit-for-purpose information materials to facilitate information diffusion.